Consulting for success : a guide for prospective consultants - Karlson, David (Crisp Pub. Menlo ParkUS, 1991)
Focuses on the prospective consultant. Details the personal characteristics of a successful consultant and describes the transition from team-player to self-employed consultant. Helps the prospective consultant to evaluate his capabilities as they relate to those required for consulting. Describes the consulting process and deals with tasks including: market research; promoting of services; determining the scope of work; and, preparing proposals, contracts, letters of agreement etc.